2011
DOI: 10.1164/rccm.201101-0089oc
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Insurance Status on Mortality and Procedural Use in Critically Ill Patients

Abstract: Rationale: Lack of health insurance may be an independent risk factor for mortality and differential treatment in critical illness. Objectives: To determine whether uninsured critically ill patients had differences in 30-day mortality and critical care service use compared with those with private insurance and to determine if outcome variability could be attributed to patient-level or hospital-level effects. Conclusions: Lack of health insurance is associated with increased 30-day mortality and decreased use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 40 publications
(35 reference statements)
5
84
1
Order By: Relevance
“…For example, a study in United States reported hospital mortality rates for critically ill patients significantly higher for the uninsured than for the insured (46), whereas in our study, homeless status had no impact on this outcome. Similarly, a systematic review reported that American uninsured patients benefited from fewer procedures in intensive care (47), as did a more recent study taking into account hospital-level effect and disease severity (48). Differences between our study results and the American situation may be due, at least in part, to the availability of a "universal healthcare guarantee" in the public French healthcare system.…”
Section: Discussionsupporting
confidence: 51%
“…For example, a study in United States reported hospital mortality rates for critically ill patients significantly higher for the uninsured than for the insured (46), whereas in our study, homeless status had no impact on this outcome. Similarly, a systematic review reported that American uninsured patients benefited from fewer procedures in intensive care (47), as did a more recent study taking into account hospital-level effect and disease severity (48). Differences between our study results and the American situation may be due, at least in part, to the availability of a "universal healthcare guarantee" in the public French healthcare system.…”
Section: Discussionsupporting
confidence: 51%
“…71 Other studies would also be useful to tease out the multiple factors that influence ICU outcomes and costs, including severity of illness, divergent therapeutic approaches, increasing physician workload, 72 and patient insurance status. 73 Despite the limitations to these data, the overall consistency of the available evidence and the rational basis for improved outcomes with enhanced experience, which is a central tenet of medical and procedural training, are compelling. Intensivists may improve outcomes through common practices, provision of urgent therapy, familiarity with acute conditions usually seen only in the critical care setting, facilitation of multidisciplinary care, increased use of evidence-based measures for prevention of complications, and provision of an ICU leadership role.…”
Section: Intensivist Versus Nonintensivist Coveragementioning
confidence: 99%
“…In the pediatric population, both Lopez et al [9] and Epstein et al [9,10] found no difference in pediatric ICU mortality based on race/ethnicity but did find that severity of illness at the time of ICU admission was higher for the uninsured and government-insured patients. Although convincing evidence for disparities in ICU health care based on race/ethnicity is lacking, most inequities in health care in the ICU seem to be based on socioeconomic status and health insurance [11][12][13][14][15]. Another outcome measurement, such as satisfaction with care and decision making, may be necessary to identify disparities within the ICU setting.…”
Section: Introductionmentioning
confidence: 99%